Primary School Feeding Programme (SFP) and Pupils’ Enrolment, Retention and Performance in Katsina State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigated the effect of primary SFP on pupils’ enrolment, retention and performance in Katsina State using survey design approach. Multistage sampling technique was used to select 542 respondents. Data were collected using structured questionnaire. Descriptive and inferential statistics were employed in data analysis. Results showed that majority were females, with NCE educational qualification, had mean age and work experience of 37 and 9 years respectively. Level of enrolment was high as pupils’ enrolment, regular and punctual school attendance increased. Also, retention level was high as pupils’ absenteeism from end of session, term exams, drop-out, leaving school before closing time, irregular school attendance reduced. Academic performance level was high following improvement in class test, term and end of session exams. Over-enrollment, ineffective supervisions of cooking environment and food preparation ranked top constraints. One way ANOVA result showed significant difference among senatorial districts on enrolment, retention and academic performance. Enrolment was significantly high in NSD than in KCSD and southern senatorial district (SSD) while retention in NSD was higher than in KSD and SSD. Similarly, NSD recorded high academic performance than KCSD that had high performance rate than SSD. The test of relationship using PPMC revealed that constraint significantly correlated with pupils’ enrolment, retention and performance levels except for retention in KCSD. Pupils’ enrolment, retention and performance have improved due to SFP. While SFP should be sustained, caterers should prepare and cook the food within the schools for collaborative quality control and supervision by teachers/headmasters and supervisors from Education Ministry